Green Supply Chain Management, Environmental Controls and Regulations in Shipping - Panayides, Photis; Alexandrou, Andria E.; Alexandrou, Stelios (My University, 2021)
This chapter provides a detailed discussion on the importance of green supply chain management (GSCM) and its connection to the shipping industry. It further addresses the important practices for the successful implementation of a GSCM strategy by shipping firms, making reference to the regulatory framework and to several of the enforcement mechanisms that exist and how these impact and enhance green shipping. It briefly considers a number of “green” regulations that lie under the umbrella of environmental preservation, while it further examines the internal and external pressures for environmental performance. The chapter also addresses maritime informatics and specifically the crucial role of digitalisation on GSCM, green performance and competitiveness in shipping.
Keywords: Environmental regulations; Ballast water management; Green shipping practices; Green supply chain management; Green supply chain integration; Environmental performance; Competitiveness; Maritime informatics; Digitalisation